Biodegradability of Cassava Edible Bioplastics in Landfill Soil and Plantation Soil - Isroi Isroi; Guntarti Supeni; Deden D. Eris; Agustina A. Cahyaningtyas (Balai Besar Kimia dan Kemasan, 2018)
Biodegrability of edible bioplastic made from cassava starch was evaluated by using landfill soil and plantation soil as natural inoculum. The edible bioplastics used in this study were bioplastic without and with addition of hydrophobic liquid. Biodegradation test of the bioplastic compared with conventional plastic samples were conducted in the glass jar for 60 days. The carbon dioxide generated from the biodegradation process absorbed by 0.1 N sodium hydroxide solutions. The carbon dioxide was titrated with 0.1 N HCl, using phenolphthalein and then followed by methyl orange as indicator. There was no carbon dioxide released from the conventional plastic during the test. Biodegradation of the bioplastic in plantation soil was higher than in landfill soil. Biodegradation rate of the bioplastic in landfill soil were 0.201 mg CO2/day and 0.249 mg CO2/day for bioplastic without and with hydrophobic liquid, respectively. Biodegradation rate of the bioplastic in plantation soil were 0.604 mg CO2/day and 0.424 mg CO2/day for bioplastic without and with hydrophobic liquid, respectively. Complete biodegradation of the bioplastic in landfill soil predicted in 431 days and 366 days, respectively. In other hand, complete biodegradation of the bioplastic in plantation soil predicted in 151 days and 201 days, respectively. Microbes population in the soil could be affected the biodegradation rate of the bioplastics.